Tinjauan Teori Pendidikan Klasik - Liyana Andriyanti, Ni Luh Putu (Jayapangus Press, 2021)
Education is not just about teaching or learning together, educators have guidelines for educating, as well as educational theories that are taught in educational science courses. Without a consistent and interconnected rational theory, actions in education are only based on coincidental, instantaneous, and irresponsible reasons. The classical educational theory consists of empiricism theory, nativism theory, naturalism theory, and convergence theory. The purpose of his article is to provide readers with an understanding of classical schools in education as well as systematic educational theory to grasp the meaning of the dynamic movement of thoughts in education. The employed data analysis method is descriptive qualitative, offering a comprehensive overview of the examination of classical education theory. The notion of empiricism posits that human growth is not contingent upon parental genetic factors, but rather on one's experiences and education. The philosophy of nativism posits that human attributes are inherent or passed down from parents. The theory of naturalism reveals that from a child was born, they have their characteristics, including their interests, talents, and abilities. Meanwhile, convergence theory is a combination of previous theories which is a combination of parental and parenting factors.